The influence of Youth and Family days and the eco-festival on the development of regenerative tourism: The example of Velika Gorica - Toth, Maja (Crisis Management Days, 2025)
In times of global challenges such as climate change, environmental degradation and deteriorating quality of life in urban areas, there is a growing need to promote sustainable development models, among which regenerative tourism is becoming an increasingly important concept. In contrast to conventional tourism, which often exploits local resources, regenerative tourism aims not only to preserve but also to actively restore the social, cultural and natural systems of communities. In this context, events that integrate ecological values, local culture, education and intergenerational connections have great potential for the development of sustainable tourism practises. The Youth and Family Days, which took place in Velika Gorica in May, are a good example of a local initiative that promotes a regenerative approach through a wide range of cultural, educational and ecological activities. The event’s programme was carefully designed to include all age groups, with a focus on educating young people, encouraging creativity, sharing leisure activities and raising awareness of active and healthy lifestyles. Through dance performances, sports tournaments, interactive workshops, environmental education and music events, the festival creates a space for dialogue, togetherness and local participation. The first day of the event was marked by the dance spectacle Good Vibrations and numerous activities in Dr Franjo Tuđman Park, where citizens of all generations gathered in a spirit of togetherness. The programme included dance performances of various styles, sports competitions, mental arithmetic workshops and creative quizzes. These activities not only promote healthy lifestyle habits, but also the active participation of children and young people in the joint creation of cultural and educational content. This strengthens the sense of community and the commitment of citizens to the development of local identity. One of the key elements of the event is its focus on ecology and sustainability. Over the following days, visitors took part in workshops such as "Dolls made from recycled material", "Brooch making", "No vegetarianism - eco-paradise" and training sessions on recycling, permaculture and climate awareness. These activities are a direct contribution to regenerative tourism as they involve the local population in learning, applying and transferring knowledge about sustainable practises. Children and young people learn how they can contribute to environmental protection through their everyday habits, and festival-goers acquire practical skills that go beyond the confines of the event. In addition, with workshops such as the “Dron Academy”, the “Gaming Zone” and “Traumatic Art”, the festival offers an innovative mix of technology, art and social engagement that appeals to a younger audience and promotes their digital, creative and presentational skills. Through such content, young people do not remain passive observers, but become active participants and creators – which is one of the basic principles of a regenerative approach to tourism and community development. Musical programmes, especially the evening concert by Damir Urban and Group 4, further enriched the festival experience, creating a strong emotional bond among visitors and enhancing the symbolic value of the public space. Cultural content such as concerts serves not only as entertainment, but also as a means of connecting and recognising shared values - which is important to create a sense of belonging and local pride, thus increasing the attractiveness of the destination for regenerative tourists. It is also important to emphasise the social dimension of the event. Youth and Family Days integrate all age groups and create a safe, inclusive and stimulating environment for shared growth and learning. The symbolic celebration of Mother’s Day through the distribution of flowers to all mothers emphasises the festival’s focus on promoting social cohesion, intergenerational solidarity and community emotional wellbeing - which is at the heart of a regenerative approach. The introduction of ESG (environmental, social and governance) principles through the selection of content, the involvement of local organisations, educational components and transparent programme management further strengthens the transformative potential of the event. While ESG principles are often associated with the business sector, they are increasingly being applied to sustainable event planning and destination management. In conclusion, the Youth and Family Days event demonstrates how the synergy of cultural, educational and environmental activities can have a concrete and positive impact on the local community and the wider tourism context. By encouraging local participation, promoting sustainable values, empowering young people and fostering intergenerational cohesion, the event not only contributes to strengthening local identity, but also actively renews and transforms the community towards sustainability, resilience and regeneration. It is precisely such initiatives that have the potential to become a model for the future development of regenerative tourism in smaller urban areas and at the local level.